A Randomized Clinical Trial Comparing Eyetronix Flicker Glass and Patching for Treatment of Amblyopia in Children Reveals Similar Improvements in Vision - Min, Seung Hyun; Chen, Shijia; Xu, Jinling; Chen, Bingzhen; Chen, Hui; Wang, Yuwen; Zhou, Jiawei; Yu, Xudong (Frontiers in Neuroscience, 2021)
Purpose Recently, Eyetronix Flicker Glass (EFG) has been introduced as a novel treatment for amblyopia. It alternatively deprives the visual input of each eye rapidly (e.g., 7 Hz). However, whether it is comparable with standard patching therapy is unclear. In this randomized clinical trial, we evaluate the efficacy of an EFG therapy as treatment for amblyopia in children and compare it to the patching therapy. Methods We tested 31 children (aged 4–13 years) with amblyopia. They were assigned into one of the two treatment groups and were treated for 12 weeks. The first group was treated with EFG for 1 h/day (Flicker Group) and the latter with a standard patch (Patching Group) for 2 h/day. We designated changes from baseline in best-corrected visual acuity (BCVA) of the amblyopic eye as our primary outcome. Changes from baseline in other visual outcomes, such as contrast sensitivity, stereopsis, and fusional vergence range were measured as secondary outcome. Results BCVA improved significantly at 12 weeks relative to baseline in both the Flicker (0.13 ± 0.11 logMAR; mean ± SD) and Patching Groups (0.21 ± 0.14 logMAR). However, the improvements were not significantly different between groups (p = 0.13). Contrast sensitivity also significantly improved at 3 and 12 cycles/degree between baseline and 12 weeks in both groups (p’s < 0.05). However, stereopsis and fusion range did not improve significantly in both groups. Conclusion An EFG therapy and patching improved BCVA similarly for children with amblyopia at 12 weeks. Both therapies improved the contrast sensitivity at 3 and 12 cycles per degree (cpd); however, only patching improved the contrast sensitivity at 6 cpd. Both therapies did not benefit binocular visual functions (stereopsis and fusional vergence range). We believe that EFG can be an additional choice for therapy. Clinical Trial Registration chictr.org number: ChiCTR2000034436.